1997
DOI: 10.1292/jvms.59.415
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Envelope Protein (E2) of Bovine Viral Diarrhea Virus in Insect Cells.

Abstract: ABSTRACT. The gene encoding the envelope glycoprotein (E2) of bovine viral diarrhea virus (BVDV) was expressed in a baculovirus. The expressed protein was detected on the surface of infected cells by immunofluorescence. Western blotting analysis showed the presence of the expressed protein of a similar molecular size to the E2 protein. The antigenicity of expressed protein were tested in guinea pigs and cattle. The immunized animals developed neutralizing antibodies against BVDV. -KEY WORDS: BVDV, envelope pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The arginine residue is also observed in the amino-acid sequence of membrane anchors of our recombinant E2. However, surface localisation of E2 has also been observed in cells infected with recombinant baculovirus [39] or recombinant VSV [21] that express E2. As suggested by Köhl et al [34,35] it is conceivable that, in some transfected cells, the cell retention machinery becomes saturated by overexpressed E2 glycoproteins which are then transported to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arginine residue is also observed in the amino-acid sequence of membrane anchors of our recombinant E2. However, surface localisation of E2 has also been observed in cells infected with recombinant baculovirus [39] or recombinant VSV [21] that express E2. As suggested by Köhl et al [34,35] it is conceivable that, in some transfected cells, the cell retention machinery becomes saturated by overexpressed E2 glycoproteins which are then transported to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralising antibodies and a cellular response are produced in animals vaccinated with various recombinant viruses expressing E2 [3,17,21], with DNA plasmid constructs expressing E2 [26,42,45] or with E2 subunit vaccines [7,11,12,39,58]. Purified recombinant E2 from BVDV1a strain Singer lead to partial protection against acute infection by the homologous strain [7].…”
Section: Bovine Viral Diarrhoea Virus (Bvdv)mentioning
confidence: 99%
“…Following transfer, the nitrocellulose membrane was blocked with TBS (0.15 M NaCl, 0.05 M Tris-HCl, pH 7.4) containing 10% skim milk for 60 min at room temperature. The membrane was then incubated for 1 hr with a 1:250 dilution of mouse sera against BVDV as described previously [12]. The membrane was washed with TBS containing 0.05% Tween 20 (TBST) and then incubated with biotin conjugated goat anti-mouse serum (KPL) for 1 hr at room temperature followed by incubation with alkaline phosphatase-conjugated streptoavidin.…”
Section: Cells and Virusmentioning
confidence: 99%
“…Previously we found that the E2 protein of BVDV expressed in baculovirus can induce neutralizing antibodies in cattle [12].…”
mentioning
confidence: 96%
See 1 more Smart Citation